Amateur Aesthetics as State Narrative in Iranian Martyrdom. Issue 1 (2nd January 2020) - Grigor, Talinn
Abstract: Focused on modern and contemporary Iranian visual culture, this article traces the shifts from an institutionalised high art ethos under the Pahlavi dynasty to a hegemonic, yet, populist-amateur cultural environment after the Iranian Revolution of 1979. By raising questions about the (dis)position of populism, amateurism, and people-made art in the streets, cemeteries, and public parks of the Islamic Republic, it proposes that, however defined and labelled, contemporary Iranian art cannot be properly understood without addressing the art historical and dialectic co-dependence of street kitsch and closeted avant-garde. In Iran, subversive art can hardly be grasped without the beauty of fake flowers.